(untitled) (International Journal of Food and Nutritional Sciences, 2019)
This paper gives a clear picture of the issues faced by the students while learning Foreign language. Students will not take much time to learn their native language when compares with non-native language. They are not in a situation to comprehend the difference between this Native and Non-Native languages. There are many reasons to discuss the influence of native language on students in learning second language. In those the first and foremost one is translating language from native to non-native. Students from primary to graduation will do the same to learn this language. They are in that impression that this is the only way to learn Foreign language. When we take this Foreign language as target language it is important to a learner to learn this language in an effective way. There are different methods help a learner to learn his/her target language. In this paper will discuss these methods in a detailed way. Students who’s medium is their mother tongue they will face many problems in learning this target language. It is very important to learn this language to a student to enter into this competitive world. One of the reasons for this is, a student cannot face an interview in his/her mother tongue. Enhancing employability skills are also very important in their professional environment. Vocabulary also plays an important role here. Increasing proficiency in his/her target language is also very important for this, he/she should inculcate a phenomenon of adopting second language learning process. Proficiency on first language is also helps a student to know better about the second language.